Depression, anxiety, and psychological distress among caregivers of young children in rural Lesotho: Associations with food insecurity, household death and parenting stress - Marguerite Marlow; Sarah Skeen; Xanthe Hunt; Phillip Sundin; Robert E. Weiss; Shoeshoe Mofokeng; Moroesi Makhetha; Lucie Cluver; Lorraine Sherr; Mark Tomlinson (Elsevier, 2022)
Good mental health is a critical resource for mothers and caregivers of young children, given the central role of mental health in enabling responsive caregiving. However, fulfilling caregiving responsibilities under challenging circumstances such as extreme poverty, food insecurity, and gender inequality intensifies vulnerability to poor mental health. Previous research focuses on mental health of mothers, while in many LMICs children are cared for by other caregivers, such as grandparents. We examined the prevalence of mental health problems among primary caregivers of young children in rural Lesotho, and investigated factors associated with these mental health problems.We analysed baseline data from a cluster randomised controlled trial, where all caregivers with children between 1 and 5 years old across 34 villages were invited to participate. The analysis included mental health data from 781 caregivers of 998 children. We assessed caregiver mental health using three self-report screening instruments. Univariate and multivariate regression modelling tested associations between caregiver, child and household variables and (1) depression symptoms (PHQ-9), (2) anxiety symptoms (GAD-7), (3) psychological distress (SRQ-20), (4) suicidal ideation and (5) help-seeking for mental health.This study reported a high prevalence of symptoms of psychological distress (46.2%), depression (25.7%), anxiety (17.1%) and suicidal ideation (27.5%) among caregivers. Greater prevalence was associated with food insecurity, parenting stress or recent death in the family/household. Older caregivers reported higher rates of psychological distress and depression, while younger caregivers reported higher rates of anxiety. Suicidal ideation was associated with greater food insecurity and parenting stress, and lower caregiver education.Our findings support the need to address intersecting public health issues to improve conditions for caregivers in these settings. Targeting modifiable risk factors such as food insecurity among individuals within a society who carry disproportionate burdens of caregiving should be prioritised, especially in contexts of scarcity, where mental health is not prioritised.